PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN PRAKTIK KERJA LAPANGAN UNIT BISNIS CENTER TERHADAP MINAT BERWIRAUSAHA - Dita Putri Cahyani; Bambang Budi Wiyono; Djum Djum Noor Benty (Universitas Negeri Malang, 2020)
Abstrak: This study aims to find out: (1) variable description of (a) entrepreneurship education, (b) fieldwork practices of the Business Center units, and (c) entrepreneurial interests, (2) positive and significant influence of education entrepreneurship on entrepreneurial interest, (3) there is a positive and significant influence of fieldwork practices in the business center unit on entrepreneurial interest, (4) as well as a positive and significant influence on entrepreneurship education and business center fieldwork practices on entrepreneurial interest. This research uses a quantitative approach with descriptive analysis and hypothesis testing. The result of study: (1) showed that there was a significant positive effect between entrepreneurship education on the entrepreneurial interest of OTKP and XK grade students in Accounting, (2) There is a significant positive effect between the work practices of the business center business units, and (3) Simultaneously there is a positive and significant influence of entrepreneurship education and fieldwork practices in the business center units on entrepreneurial interest. keywords: entrepreneurship education, fieldwork practices, interest in entrepreneurship Abstrak: Penelitian ini bertujuan untuk mengetahui: (1) deskripsi variabel tentang (a) pendidikan kewirausahaan, (b) praktik kerja lapangan Unit Bisnis Center, dan (c) minat berwirausaha, (2) adanya pengaruh positif dan signifikan pendidikan kewirausahaan terhadap minat berwirausaha, (3) adanya pengaruh positif dan signifikan praktik kerja lapangan di unit bisnis center terhadap minat berwirausaha, (4) serta adanya pengaruh positif dan signifikan pendidikan kewirausahaan dan praktik kerja lapangan unit bisnis center terhadap minat berwirausaha. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis deskriptif dan uji hipotesis. Hasil Penelitian menujukkan adanya pengaruh positif yang signifikan antara pendidikan kewirausahaan terhadap minat berwirausaha siswa kelas XI OTKP dan Akuntansi. Ada pengaruh positif yang signifikan antara praktik kerja lapangan unit bisnis center terhadap minat berwirausaha. Secara simultan terdapat pengaruh positif dan signifikan pendidikan kewirausahaan dan praktik kerja lapangan di unit bisnis center terhadap minat berwirausaha. kata kunci : pendidikan kewirausahaan, praktik kerja lapangan, minat berwirausaha